Stakeholder mapping: advancing research on sexual and reproductive health policies and income protection for cisgender and transgender female sex workers in Buenos Aires, Argentina - Panizoni, Estefania; Esandi, María Eugenia; Zalazar, Virginia; Aristegui, Ines; Argüello, Agustina; Cardozo, Nadir; Orellano, Georgina; Romero, Marcela; Loutfy, Mona; Walmsley, Sharon; Fink, Valeria; Duran, Adriana; et al. (Frontiers in Public Health, 2025)
IntroductionIn the initial steps towards the development of an implementation project aimed to support sexual and reproductive health (SRH) policies and income protection for cisgender and transgender sex workers in the Ciudad Autónoma de Buenos Aires (CABA), we employed stakeholder mapping. This is a crucial tool in health policy and systems and research to identify, categorize, and characterize key stakeholders involved in policy planning and implementation.MethodsProspective stakeholder mapping was conducted between February and September 2023 through a series of internal meetings and consultations with relevant community organizations to identify key stakeholders involved in SRH of female sex workers (FSWs) in CABA. The stakeholder mapping included three stages: 1. Identification and categorization of stakeholders using primary and secondary sources; 2. Analysis of stakeholder knowledge, level of agreement/interest, and level of influence/power; and 3. Characterization of stakeholder positioning. The absolute and relative frequencies of key stakeholders were estimated, and the average values of knowledge, power/influence, and interest/agreement were calculated for each category. The results were represented in a matrix identifying six types of positions (promoter, supporter, neutral, observer, high-risk blocker, low-risk blocker).ResultsA total of 147 key actors were identified across sectors, including government, civil society, academia, abolitionist community organizations, health services, media and national and jurisdictional governments. Only four categories had detailed knowledge of the SRH situation and policies focused on FSWs. The stakeholders were categorized as 16% as promoters, 68% as supporters, 10% as blockers, 3% as observers, and 3% as neutral. Among promoters, national and jurisdictional governments stood out, while the supporters included the FSWs and the civil society organizations representing them, who also actively participated in the mapping process. Blockers mainly included abolitionist community organizations and security forces.DiscussionStakeholder mapping proved to be a valuable tool for understanding the political landscape while ethically centering the voices of FSWs. The findings support the development of inclusive, context-sensitive policies and provide a replicable methodology for similar initiatives in other socio-political contexts.